Epidemiological cut‐off values for itraconazole and ravuconazole for Madurella mycetomatis, the most common causative agent of mycetoma. Issue 12 (25th August 2022) - Nyuykonge, Bertrand; Siddig, Emmanuel E.; Mhmoud, Najwa Adam; Nyaoke, Borna A.; Zijlstra, Eduard E.; Verbon, Annelies; Bakhiet, Sahar; Fahal, Ahmed H.; van de Sande, Wendy W. J.
Abstract: Background: Eumycetoma is a neglected tropical disease. It is a chronic inflammatory subcutaneous infection characterised by painless swellings which produce grains. It is currently treated with a combination of itraconazole and surgery. In an ongoing clinical study, the efficacy of fosravuconazole, the prodrug of ravuconazole, is being investigated. For both itraconazole and ravuconazole, no clinical breakpoints or epidemiological cut‐off values (ECV) to guide treatment are currently available. Objective: To determine tentative ECVs for itraconazole and ravuconazole in Madurella mycetomatis, the main causative agent of eumycetoma. Materials and Methods: Minimal inhibitory concentrations (MICs) for itraconazole and ravuconazole were determined in 131 genetically diverse clinical M. mycetomatis isolates with the modified CLSI M38 broth microdilution method. The MIC distributions were established and used to determine ECVs with the ECOFFinder software. CYP51A sequences were sequenced to determine whether mutations occurred in this azole target gene, and comparisons were made between the different CYP51A variants and the MIC distributions. Results: The MICs ranged from 0.008 to 1 mg/L for itraconazole and from 0.002 to 0.125 mg/L for ravuconazole. The M. mycetomatis ECV for itraconazole was 1 mg/L and for ravuconazole 0.064 mg/L. In the wild‐type population, two CYP51A variants were found for M. mycetomatis, which differed in one amino acid at position 499 (S499G). The MIC distributions for itraconazole and ravuconazole were similar between the two variants. No mutations linked to decreased susceptibility were found. Conclusion: The proposed M. mycetomatis ECV for itraconazole is 1 mg/L and for ravuconazole 0.064 mg/L.